Effects of a high-pressure treatment on bovine gamma globulin and its reduction in allergenicity - Yamamoto, S., Niigata Univ. (Japan); Mikami, N; Matsuno, M; Hara, T; Odani, S; Suzuki, A; Nishiumi, T (Bioscience, biotechnology, and biochemistry, 2010)
The effects of a high-pressure treatment on the IgE-specific binding activity and structural changes to bovine gamma globulin (BGG), a beef allergen, were investigated. The allergenicity of pressure-treated BGG was also evaluated. We found that the IgE-specific binding activity and allergenicity of BGG were decreased by the high-pressure treatment. Almost no significant change in secondary structure was apparent for pressurized BGG, but a change in the tertiary structure was detected. The decreased IgE-specific binding activity and allergenicity of pressurized BGG were probably due to changes in the tertiary structure caused by pressurization. The results of this study suggest that a high-pressure treatment would be an effective food-processing technique to reduce the allergenicity of BGG.